Wooden Objects in Architecture Competitions - Arnoldas Gabrėnas; Darius Linartas (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2020)
The article deals with the role of wooden architecture constructions in competitions that took place in the recent decade. Architecture competitions for which designs from wood were offered are discussed. The properties of such constructions and their results in the competition, as well as the subsequent phases of the existence of a design, if any, are singled out. It should be noted that wooden constructions, owing to their properties, are increasingly noticeable and are acknowledged with awards. Given that this process takes place in architecture competitions, we can predict architectural trends in the near future.